Protocol for a randomized controlled trial on the impact of a health action process approach model-based mobile health intervention via WeChat on health behaviors of brucellosis patients - Wang, Jing; Jiang, Yang; Yu, Zhenjie; Chen, Jiawei (Frontiers in Public Health, 2025)
BackgroundBrucellosis is a common zoonotic disease and a significant public health concern. Effective health management is essential for improving the self-management behaviors of brucellosis patients. This study aims to assess the effectiveness of a mobile health (mHealth) intervention based on the Health Action Process Approach (HAPA) model in enhancing self-management among brucellosis patients.MethodsThis single-center, single-blind randomized controlled trial will be conducted at the Fourth Central Hospital of Baoding City, Hebei Province, China (ChiCTR2300071152). A total of 58 participants will be randomly assigned to the mHealth intervention group or the routine education group. Inclusion criteria: (1) Aged ≥18 years, (2) Diagnosed with brucellosis, (3) Familiar with WeChat, (4) Voluntary consent. Exclusion criteria include severe comorbidities, psychotropic medication use, and pregnancy. The intervention will be delivered via WeChat, using educational materials such as articles, videos, and case studies. The control group will receive standard discharge education. Primary outcomes include health behavior formation and health literacy, and secondary outcomes include psychological variables and behavior change. Statistical analyses will be conducted using SPSS Statistics 26.0. Data will be expressed as mean ± standard deviation or count (%). Parametric or non-parametric tests will be used as appropriate, and missing data will be handled using multiple imputation methods. A p-value <0.05 will be considered statistically significant.DiscussionThis study will contribute to understanding the application of the HAPA model in guiding health interventions for brucellosis patients. It will be the first study in China to apply the HAPA model in this context, providing insights into its effectiveness for improving health behaviors and long-term outcomes in brucellosis patients.